Design and experimental characterization of a metamaterial-assisted monopole antenna - Lima, Larissa Cristiane Paiva de Sousa (2014)
In recent years a new class of materials, the metamaterials, has emerged in the scientific community. The use of these materials makes possible to achieve unique electromagnetic properties, such as the negative refractive index. Today there exist several applications that take advantage of these special properties, such as sensors, antennas and invisibility cloaks, aiming at improving their intrinsic characteristics. Based on these considerations, this project aims at developing metamaterials structures to control the radiation properties of antennas in the microwave range, such as gain and directivity. More specifically, it was also chosen chiral metamaterials, mainly due to the phenomenon of electromagnetic field rotation which opens the possibility to control efficiently the radiation properties of antennas. In addition, chiral metamaterials, which have proved to be a more attractive alternative to obtain negative or zero refractive index, enable a greater degree of freedom in the design of different structures. This work encompasses all different phases of the structure design, namely: project, computational modeling, fabrication, and characterization of the proposed structures. We show improvements for the gain that in some cases reaches more than the double of the conventional monopole antenna gain and for the return loss parameter, which reaches minimum values. We also could maintain good efficiency and improve the input impedance matching. Finally, it is worth mentioning that this new technology also has the great potential to be applied in the telecommunication devices, particularly to improve communications based on antennas.